2008
DOI: 10.1086/529066
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Unmagnetized and Magnetized Shear Layers

Abstract: We present numerical simulations of the growth and saturation of the Kelvin-Helmholtz instability in a compressible fluid layer with and without a weak magnetic field. In the absence of a magnetic field, the instability generates a single eddy which flattens the velocity profile, stabilizing it against further perturbations. Adding a weak magnetic field - weak in the sense that it has almost no effect on the linear instability - leads to a complex flow morphology driven by MHD forces and to enhanced broadening… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 27 publications
(41 reference statements)
3
36
0
Order By: Relevance
“…11(c, f ), the mean flow evolution is substantially different, with mixing of momentum over a wider region (about twice as wide as for the hydrodynamic case), leaving smaller shears near the centre of the channel. This is consistent with previous studies [e.g., 16].…”
Section: A Mean Flow Changessupporting
confidence: 94%
See 1 more Smart Citation
“…11(c, f ), the mean flow evolution is substantially different, with mixing of momentum over a wider region (about twice as wide as for the hydrodynamic case), leaving smaller shears near the centre of the channel. This is consistent with previous studies [e.g., 16].…”
Section: A Mean Flow Changessupporting
confidence: 94%
“…, 7]. However, in the presence of a background magnetic field, various studies have shown how vortices can be disrupted, by which we mean either a reduction in strength or spatial coherence, or completely destroyed [8][9][10][11][12][13][14][15][16]. Here we show explicitly how this disruption depends on both the field strength and on the magnetic Reynolds number Rm.…”
Section: Introductionmentioning
confidence: 76%
“…This is definitely the most extreme case: magnetic field components parallel to the shear flows can stabilize against the KHI, and for compressible flows, the system will be stable for all those wavenumbers whose effective Mach number is larger than some critical value (Gerwin 1968). For a recent detailed discussion of the KHI, see, e.g., Palotti et al (2008).…”
Section: Kelvin-helmholtz Instabilitymentioning
confidence: 99%
“…This is an interesting problem in its own right. Hughes & Tobias (2001) considered the linear evolution of magnetized shear instabilities, whilst the non-linear problem has also been studied in unstratified compressible fluids (Frank et al 1996;Ryu, Jones & Frank 2000;Palotti et al 2008) as well as in isothermal stratified layers (Brüggen & Hillebrandt 2001). The recent review article by Gilman & Cally (2007) describes global magnetohydrodynamic shear instabilities in the tachocline.…”
Section: Introductionmentioning
confidence: 99%